Offshore pipelines - Guo, Boyun (Elsevier/Gulf Professional Pub., 2005)
More than a third of the worldwide growth in drilling is expected to come from offshore, making the development of offshore pipelines an extremely hot topic in the energy industry. Offshore Pipelines is the most up-to-date reference for engineers and developers challenged with bringing oil and gas onshore. Written primarily for engineers and management personnel working on offshore and deepwater oil and gas pipelines, this book brings together the authors years of experience on a variety of pipeline projects. It offers cost-effective approaches for developing pipeline systems. By presenting principles, criteria, and data necessary to perform engineering analyses, the authors set forth guidelines that can be employed to optimize pipeline development projects. Covers the full scope of pipeline development from pipeline designing, installing, and testing to operation. Guidelines to achieve cost-effective management of offshore and deepwater pipeline development and operations. Tips on how to design low-cost pipelines allowing long-term operability and safety.
Keywords: Petroleum pipelines -- Design and construction.; Gas pipelines -- Design and construction.; Offshore structures.; elektronické knihy; electronic books